Operationalising resilience-based management at scale: A meta-adaptive blueprint from the Great Barrier Reef crown-of-thorns starfish control program - Samuel A. Matthews; Michael Bode; Roger Beeden; Mary C. Bonin; Cameron S. Fletcher; Brigid Kerrigan; Isobel Ryan; Jennifer Wilmes; Alice White; David H. Williamson (Biological Conservation, 2026)

Larval dispersal models predict reefs that experience crown-of-thorns starfish outbreaks receive more larvae - Owen Stewart; Adam T. Downie; Severine Choukroun; Michael Bode (Coral Reefs, 2026)
Crown-of-thorns starfish (COTS) are a leading cause of coral decline on the Great Barrier Reef (GBR), with the majority of their impact occurring during outbreaks. These outbreaks involve rapid increases in populations followed by abrupt declines, and spread between reefs via larval dispersal—a key process in COTS reproduction. Given the difficulty in quantifying dispersal empirically, predictions are instead formed using coupled models of ocean currents and larval biology. Previous efforts have linked dispersal models to COTS population dynamics, however do so indirectly, or at spatiotemporally limited scales. Using an improved set of dispersal estimates and expanded COTS monitoring data, we assess the role of dispersal in determining a reef’s susceptibility to outbreaks. Our results indicate that while there is minimal evidence that dispersal patterns alone drive outbreaks, once combined with COTS population data it becomes clear that dispersal still plays a major role. By predicting COTS populations on undersampled reefs, we estimate that, on average, reefs that have experienced an outbreak receive 50–100% more larvae than those that have not. This is irrespective of whether we assume reefs hold their long-term predicted average COTS abundance, or their predicted maximum abundance. Given the difficulty in directly validating dispersal models, these results provide evidence that highlights their utility in understanding marine population dynamics. Furthermore, our results emphasise the critical role of resolving dispersal networks in guiding COTS control efforts. Specifically, they indicate that suppressing larval production through culling may reduce the risk of outbreaks on downstream reefs connected via larval dispersal.

Calibrated Ecosystem Models Cannot Predict the Consequences of Conservation Management Decisions—Clarification - Larissa Lubiana Botelho; Cailan Jeynes‐Smith; Sarah A. Vollert; Michael Bode (Ecology Letters, 2025)
Woodstock and Harris raise concerns about generalisations in our paper ‘Calibrated Ecosystem Models Cannot Predict the Consequences of Conservation Management Decisions’. They implied that our conclusions are invalidated by the exclusion of density dependent compensatory feedback and the existence of automated calibration approaches with overfitting penalties—claims that overlook the broader structural issues we identified. Here, we explore their key criticism in more detail, clarify our position and explain why we continue to stand by our findings.

Direct resistive heating of a catalytic fixed-bed reactor for ethanol dehydration - Emre Turan; Robert Dieckmann; Michael Geske; Raoul Naumann d’Alnoncourt; Michael Bender; Johannes Bode; Benjamin Frank; Dina Zakgeym; Grigorios Kolios; Frank Rosowski (Chemical Engineering Journal, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Larval dispersal predictions are highly sensitive to hydrodynamic modelling choices - Severine Choukroun; Owen B. Stewart; Luciano B. Mason; Michael Bode (Coral Reefs, 2025)
Larval dispersal is a critical ecological process in marine ecosystems, responsible for connecting and replenishing populations in patchy habitat. Because empirical measurements of larval dispersal are very challenging, coupled biological and oceanographic simulations (“biophysical models”) of larval dispersal are commonly used to answer ecological questions and support conservation management decisions. In the process of creating biophysical models, a series of choices must be made that do not have a single correct answer—sometimes because the oceanographic or ecological processes are uncertain; sometimes because trade-offs are required between different goals (e.g. computational time versus spatial resolution). In this paper, we demonstrate that larval dispersal estimates at management scales are strongly affected by these choices. Using three different hydrodynamic models of the Great Barrier Reef, we estimated the dispersal of crown-of-thorns starfish larvae in the spawning seasons between 2018 and 2021. Despite sharing similar physical forcings and using similar models of larval behaviour, we find that the different hydrodynamic models produce divergent predictions of larval dispersal between the reefs. If used to support crown-of-thorns starfish control decisions, these different predictions would recommend different priority reefs. Our results caution against the use of single models of larval dispersal, and suggest that multi-model ensembles may offer a valuable new perspective on dispersal patterns in marine environments.

Measuring the performance of Antarctic Treaty decision‐making - Natasha Blaize Gardiner; Neil Gilbert; Daniela Liggett; Michael Bode (Conservation Biology, 2025)
Agreements reached at the Antarctic Treaty Consultative Meetings (ATCMs) are among the primary means for addressing Antarctic conservation and environmental protection issues. However, according to contemporary scholars, Antarctic Treaty decision‐making is becoming increasingly unresponsive to the rising environmental challenges in the region. We assessed the performance of Antarctic Treaty decision‐making by measuring the rate and diversity of decision‐making over the last 6 decades. To measure the rate, we counted the number of inputs and outputs of ATCMs and calculated the time taken for legally binding outputs to enter into force. To measure diversity, we calculated the range of topics addressed by the inputs and outputs of ATCMs. The average number of agreements reached per ATCM increased from 1961 to 2022. Although the diversity of Antarctic topics discussed at ATCMs remained consistently high, the diversity of topics on which legally binding agreements were adopted declined significantly. Antarctic issues—including those of highest priority—are now almost entirely dealt with through nonbinding, soft‐law agreements. It is plausible that this move away from binding decisions reflects a dynamic governance institution evolving to respond to new pressures. However, we suggest that the change reveals a concerning shift in decision‐making behavior and performance, unique to the treaty's history. Soft law is beneficial in some cases, but its overuse diminishes accountability and transparency, significantly reducing the parties’ abilities to understand and measure their performance, including the outcomes and impacts of decisions. Although the rate and diversity of ATCM inputs and outputs provide only a partial view of decision‐making performance, the exploration of these metrics provides a foundation for asking essential questions about the impacts of Antarctic Treaty governance on the region's environmental protection and conservation.

Calibrated Ecosystem Models Cannot Predict the Consequences of Conservation Management Decisions - Larissa Lubiana Botelho; Cailan Jeynes‐Smith; Sarah A. Vollert; Michael Bode (Ecology Letters, 2025)
Ecosystem models are often used to predict the consequences of management interventions in applied ecology and conservation. These models are often high‐dimensional and nonlinear, yet limited data are available to calibrate or validate them. Consequently, their utility as decision‐support tools is unclear. In this paper, we calibrate ecosystem models to time series data from 110 different experimental microcosm ecosystems, each containing three to five interacting species. Then, we assess their ability to predict the consequences of management interventions. Our results show that for each time series dataset, multiple divergent parameter sets offer equivalent, good fits. However, these models have poor predictive accuracy when forecasting future dynamics or when predicting how the ecosystem will respond to management intervention. Closer inspection reveals that the models fail because calibration cannot determine the nature of the interspecific interactions. Our findings question whether ecosystem models can support applied ecological decision‐making when calibrated against real‐world datasets.

Identifying and explaining resilience in ecological networks - Cailan Jeynes‐Smith; Michael Bode; Robyn P. Araujo (Ecology Letters, 2024)
Resilient ecological systems are more likely to persist and function in the Anthropocene. Current methods for estimating an ecosystem's resilience rely on accurately parameterized ecosystem models, which is a significant empirical challenge. In this paper, we adapt tools from biochemical kinetics to identify ecological networks that exhibit ‘structural resilience’, a strong form of resilience that is solely a property of the network structure and is independent of model parameters. We undertake an exhaustive search for structural resilience across all three‐species ecological networks, under a generalized Lotka‐Volterra modelling framework. Out of 20,000 possible network structures, approximately 2% display structural resilience. The properties of these networks provide important insights into the mechanisms that could promote resilience in ecosystems, provide new theoretical avenues for qualitative modelling approaches and provide a foundation for identifying robust forms of ecological resilience in large, realistic ecological networks.

Characterization of emissions from axle-mounted rail disc brakes - Daniel Fruhwirt; Thomas Nöst; Philipp Leonhardt; Martin Leitner; Peter Brunnhofer; Gina Bode; Sabrina Michael; Johannes Rodler (Transportation Research Part D: Transport and Environment, 2024)

Dispersal patterns of sandfish (Holothuria scabra) larvae in Manus Province, Papua New Guinea - Peter Waldie; David A. Feary; Michael Bode; Manuai Matawai; Hugo B. Harrison; Michael L. Berumen; Chris Molai; Maunoa Karo; Richard J. Hamilton (Frontiers in Marine Science, 2024)
In many tropical nations, coastal communities seek to manage their sea cucumber fisheries by establishing locally managed marine areas on their traditional fishing grounds. These managed areas can protect spawning stocks, however the extent to which they help to replenish nearby sea cucumber fisheries is debated, as nothing is known about the scales at which sea cucumber larvae disperse. In this study, we used genetic parentage analyses and statistical modelling to provide the first empirical measure of larval dispersal patterns for a sea cucumber species. We analysed tissue samples from 765 adult and 827 juvenile sandfish ( Holothuria scabra ) collected from five traditional fishing grounds of the Titan tribe, from Manus Province, Papua New Guinea. All adults were sampled from the Pere fishing grounds (the larval source area), with juveniles sampled from the Pere, Mbunai, Tawi, Timonai and Mbuke fishing grounds. Parentage analysis identified 15 juveniles that were the offspring of parents sampled from Pere fishing grounds, with six of these juveniles located in the same fishing grounds as their parents. The best-fit larval dispersal kernel predicted that the average H. scabra larvae travelled 15 km from its spawning location, with 50% of larvae settling within 6.7 km of their parents and 95% of larvae settling within 59 km of their parents. These results suggest that the Titan tribes’ desire to protect their H. scabra spawning stocks by establishing a network of locally managed marine areas across 65 km of continuous coastline is a culturally appropriate strategy, which has merit from both an ecological and fisheries standpoint.

Methane pyrolysis in packed bed reactors: Kinetic modeling, numerical simulations, and experimental insights - Manas Mokashi; Akash Bhimrao Shirsath; Ahmet Çelik; Patrick Lott; Heinz Müller; Steffen Tischer; Lubow Maier; Johannes Bode; David Schlereth; Frederik Scheiff; Dieter Flick; Michael Bender; et al. (Chemical Engineering Journal, 2024)

BoundED: Neural boundary and edge detection in 3D point clouds via local neighborhood statistics - Lukas Bode; Michael Weinmann; Reinhard Klein (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

PM emissions from railways – Results of tests on a wheel-rail test bench - Daniel Fruhwirt; Peter Sturm; Thomas Nöst; Philip Leonhardt; Gina Bode; Sabrina Michael; Johannes Rodler (Transportation Research Part D: Transport and Environment, 2023)

Emissions from railways: Results of tests on a pantograph-catenary test bench - Daniel Fruhwirt; Peter Sturm; Giuseppe Bucca; Gina Bode; Sabrina Michael; Johannes Rodler (Transportation Research Part D: Transport and Environment, 2023)

Designing an expert-led Bayesian network to understand interactions between policy instruments for adoption of eco-friendly farming practices - Helen J. Mayfield; Rachel Eberhard; Christopher Baker; Umberto Baresi; Michael Bode; Anthea Coggan; Angela J. Dean; Felicity Deane; Evan Hamman; Diane Jarvis; Barton Loechel; Bruce M. Taylor; et al. (Environmental Science & Policy, 2023)

Modeling total predation to avoid perverse outcomes from cat control in a data‐poor island ecosystem - Michaela Plein; Katherine R. O'Brien; Matthew H. Holden; Matthew P. Adams; Christopher M. Baker; Nigel G. Bean; Scott A. Sisson; Michael Bode; Kerrie L. Mengersen; Eve McDonald‐Madden (Conservation Biology, 2022)
Data‐hungry, complex ecosystem models are often used to predict the consequences of threatened species management, including perverse outcomes. Unfortunately, this approach is impractical in the many systems that have insufficient data to parameterize ecosystem interactions or reliably calibrate or validate such models. We devised a different approach composed of a minimum realistic model that guides decisions in data‐ and resource‐scarce systems. We applied our approach to a case study in an invaded ecosystem from Christmas Island, Australia, where there are concerns that cat ( Felis catus ) eradication to protect native species, including the red‐tailed tropicbird ( Phaethon rubricauda ), could release mesopredation by invasive rats ( Rattus rattus ). We used biophysical constraints (metabolic demand) and observable parameters (e.g., prey preferences) to identify the combined cat and rat abundances that could threaten the tropicbird population. The population of tropicbirds was not sustained when predated by 1607 rats (95% credible interval [CI]: 103–5910) in the absence of cats and 21 cats (95% CI: 2–82) in the absence of rats. For every cat removed from the island, the bird's net population growth rate improved, provided rats did not increase by more than 77 individuals (95% CI: 30–174). Thus, in this context, 1 cat is equivalent to 30–174 rats. Our methods are especially useful for on‐the‐ground predator control in the absence of knowledge of predator–predator interactions to determine whether current abundance of predators threatened the prey population of interest; managing only 1 predator species was sufficient to protect the prey species given potential release of another predator; and control of multiple predator species was needed to meet the conservation goal. With our approach limited information can be used for maximum value in data‐poor systems because it shifts the focus from predicting future trajectories to identifying conditions that impede conservation.

Roman lead ingots from Macedonia—the Augustan shipwreck of Comacchio (prov. Ferrara, Italy) and the reinterpretation of its lead ingots’ provenance deduced from lead isotope analysis - Michael Bode; Norbert Hanel; Peter Rothenhöfer (Archaeological and Anthropological Sciences, 2021)
A shipwreck of the 3rd/2nd decade BC found near Comacchio (prov. Ferrara, Italy) in 1980 contained not only well-preserved technical equipment and commercial goods but also 102 Roman lead ingots. Since then, the origin of the ingots has been intensively discussed. Domergue et al. (2012) connected the epigraphic elements with lead isotope analyses and favored the southeastern Spanish lead ore mines being the source of the lead metal. An origin from the Balkan region (Illyricum) was favored by Dušanić (2008). Due to our investigations, both assumptions cannot be maintained. We present a new interpretation of the lead’s isotope signature which best match data of ore deposits from Chalkidiki, Thasos island, and Pangaion mountains in the northern Aegean region.

The spatial footprint and patchiness of large‐scale disturbances on coral reefs - Andreas Dietzel; Sean R. Connolly; Terry P. Hughes; Michael Bode (Global Change Biology, 2021)
Ecosystems have always been shaped by disturbances, but many of these events are becoming larger, more severe and more frequent. The recovery capacity of depleted populations depends on the frequency of disturbances, the spatial distribution of mortality and the scale of dispersal. Here, we show that four mass coral bleaching events on the Great Barrier Reef (in 1998, 2002, 2016 and 2017) each had markedly larger disturbance footprints and were less patchy than a severe category 5 tropical cyclone (Cyclone Yasi, 2011). Severely bleached reefs in 2016 and 2017 were isolated from the nearest lightly affected reefs by up to 146 and 200 km, respectively. In contrast, reefs damaged by Cyclone Yasi were on average 20 km away from relatively undisturbed reefs, well within the estimated range of larval dispersal for most corals. Based on these results, we present a model of coral reef disturbance and recovery to examine (1) how the spatial clustering of disturbances modifies large‐scale recovery rates; and (2) how recovery rates are shaped by species' dispersal abilities. Our findings illustrate that the spatial footprint of the recent mass bleaching events poses an unprecedented threat to the resilience of coral species in human history, a threat that is even larger than the amount of mortality suggests.

Discovery of a major QTL for root-knot nematode (Meloidogyne incognita) resistance in cultivated sweetpotato (Ipomoea batatas) - Bonny Michael Oloka; Guilherme da Silva Pereira; Victor A. Amankwaah; Marcelo Mollinari; Kenneth V. Pecota; Benard Yada; Bode A. Olukolu; Zhao-Bang Zeng; G. Craig Yencho (Theoretical and Applied Genetics, 2021)
Key message Utilizing a high-density integrated genetic linkage map of hexaploid sweetpotato, we discovered a major dominant QTL for root-knot nematode (RKN) resistance and modeled its effects. This discovery is useful for development of a modern sweetpotato breeding program that utilizes marker-assisted selection and genomic selection approaches for faster genetic gain of RKN resistance. Abstract The root-knot nematode [Meloidogyne incognita (Kofoid & White) Chitwood] (RKN) causes significant storage root quality reduction and yields losses in cultivated sweetpotato [Ipomoea batatas (L.) Lam.]. In this study, resistance to RKN was examined in a mapping population consisting of 244 progenies derived from a cross (TB) between ‘Tanzania,’ a predominant African landrace cultivar with resistance to RKN, and ‘Beauregard,’ an RKN susceptible major cultivar in the USA. We performed quantitative trait loci (QTL) analysis using a random-effect QTL mapping model on the TB genetic map. An RKN bioassay incorporating potted cuttings of each genotype was conducted in the greenhouse and replicated five times over a period of 10 weeks. For each replication, each genotype was inoculated with ca. 20,000 RKN eggs, and root-knot galls were counted ~62 days after inoculation. Resistance to RKN in the progeny was highly skewed toward the resistant parent, exhibiting medium to high levels of resistance. We identified one major QTL on linkage group 7, dominant in nature, which explained 58.3% of the phenotypic variation in RKN counts. This work represents a significant step forward in our understanding of the genetic architecture of RKN resistance and sets the stage for future utilization of genomics-assisted breeding in sweetpotato breeding programs.

Using ensemble modeling to predict the impacts of assisted migration on recipient ecosystems - Katie Peterson; Michael Bode (Conservation Biology, 2021)
Assisted migration is a controversial conservation measure that aims to protect threatened species by moving part of their population outside its natural range. Although this could save species from extinction, it also introduces a range of risks. The magnitude of the threat to recipient ecosystems has not been investigated quantitatively, despite being the most common criticism leveled at the action. We used an ensemble modeling framework to estimate the risks of assisted migration to existing species within ecosystems. With this approach, we calculated the consequences of an assisted migration project across a very large combination of translocated species and recipient ecosystems. We predicted the probability of a successful assisted migration and the number of local extinctions would result from establishment of the translocated species. Using an ensemble of simulated 15‐species recipient ecosystems, we estimated that translocated species will successfully establish in 83% of cases if introduced to stable, high‐quality habitats. However, assisted migration projects were estimated to cause an average of 0.6 extinctions and 5% of successful translocations triggered 4 or more local extinctions. Quantifying the impacts to species within recipient ecosystems is critical to help managers weigh the benefits and negative consequences of assisted migration.

A locust embryo as predictive developmental neurotoxicity testing system for pioneer axon pathway formation - Karsten Bode; Maja Bohn; Jennifer Reitmeier; Philine Betker; Michael Stern; Gerd Bicker (Archives of Toxicology, 2020)

Simultaneous invasive alien predator eradication delivers the best outcomes for protected island species - Christopher M. Baker; Michaela Plein; Rabith Shaikh; Michael Bode (Biological Invasions, 2020)

Correction to: Ocean zoning within a sparing versus sharing framework - Jennifer McGowan; Michael Bode; Matthew H. Holden; Katrina Davis; Nils C. Krueck; Maria Beger; Katherine L. Yates; Hugh P. Possingham (Theoretical Ecology, 2018)

Ocean zoning within a sparing versus sharing framework - Jennifer McGowan; Michael Bode; Matthew H. Holden; Katrina Davis; Nils C. Krueck; Maria Beger; Katherine L. Yates; Hugh P. Possingham (Theoretical Ecology, 2018)

Using Hidden Markov Models to characterise intermittent social behaviour in fish shoals - Nikolai W. F. Bode; Michael J. Seitz (The Science of Nature, 2018)

Minimizing species extinctions through strategic planning for conservation fencing - Jeremy L. Ringma; Brendan Wintle; Richard A. Fuller; Diana Fisher; Michael Bode (Conservation Biology, 2017)
Conservation fences are an increasingly common management action, particularly for species threatened by invasive predators. However, unlike many conservation actions, fence networks are expanding in an unsystematic manner, generally as a reaction to local funding opportunities or threats. We conducted a gap analysis of Australia's large predator‐exclusion fence network by examining translocation of Australian mammals relative to their extinction risk. To address gaps identified in species representation, we devised a systematic prioritization method for expanding the conservation fence network that explicitly incorporated population viability analysis and minimized expected species’ extinctions. The approach was applied to New South Wales, Australia, where the state government intends to expand the existing conservation fence network. Existing protection of species in fenced areas was highly uneven; 67% of predator‐sensitive species were unrepresented in the fence network. Our systematic prioritization yielded substantial efficiencies in that it reduced expected number of species extinctions up to 17 times more effectively than ad hoc approaches. The outcome illustrates the importance of governance in coordinating management action when multiple projects have similar objectives and rely on systematic methods rather than expanding networks opportunistically.

Reef-fish larval dispersal patterns validate no-take marine reserve network connectivity that links human communities - Rene A. Abesamis; Pablo Saenz-Agudelo; Michael L. Berumen; Michael Bode; Claro Renato L. Jadloc; Leilani A. Solera; Cesar L. Villanoy; Lawrence Patrick C. Bernardo; Angel C. Alcala; Garry R. Russ (Coral Reefs, 2017)

Ensemble ecosystem modeling for predicting ecosystem response to predator reintroduction - Christopher M. Baker; Ascelin Gordon; Michael Bode (Conservation Biology, 2017)
Introducing a new or extirpated species to an ecosystem is risky, and managers need quantitative methods that can predict the consequences for the recipient ecosystem. Proponents of keystone predator reintroductions commonly argue that the presence of the predator will restore ecosystem function, but this has not always been the case, and mathematical modeling has an important role to play in predicting how reintroductions will likely play out. We devised an ensemble modeling method that integrates species interaction networks and dynamic community simulations and used it to describe the range of plausible consequences of 2 keystone‐predator reintroductions: wolves (Canis lupus) to Yellowstone National Park and dingoes (Canis dingo) to a national park in Australia. Although previous methods for predicting ecosystem responses to such interventions focused on predicting changes around a given equilibrium, we used Lotka–Volterra equations to predict changing abundances through time. We applied our method to interaction networks for wolves in Yellowstone National Park and for dingoes in Australia. Our model replicated the observed dynamics in Yellowstone National Park and produced a larger range of potential outcomes for the dingo network. However, we also found that changes in small vertebrates or invertebrates gave a good indication about the potential future state of the system. Our method allowed us to predict when the systems were far from equilibrium. Our results showed that the method can also be used to predict which species may increase or decrease following a reintroduction and can identify species that are important to monitor (i.e., species whose changes in abundance give extra insight into broad changes in the system). Ensemble ecosystem modeling can also be applied to assess the ecosystem‐wide implications of other types of interventions including assisted migration, biocontrol, and invasive species eradication.

Large‐scale, multidirectional larval connectivity among coral reef fish populations in the Great Barrier Reef Marine Park - David H. Williamson; Hugo B. Harrison; Glenn R. Almany; Michael L. Berumen; Michael Bode; Mary C. Bonin; Severine Choukroun; Peter J. Doherty; Ashley J. Frisch; Pablo Saenz‐Agudelo; Geoffrey P. Jones (Molecular Ecology, 2016)
Larval dispersal is the key process by which populations of most marine fishes and invertebrates are connected and replenished. Advances in larval tagging and genetics have enhanced our capacity to track larval dispersal, assess scales of population connectivity, and quantify larval exchange among no‐take marine reserves and fished areas. Recent studies have found that reserves can be a significant source of recruits for populations up to 40 km away, but the scale and direction of larval connectivity across larger seascapes remain unknown. Here, we apply genetic parentage analysis to investigate larval dispersal patterns for two exploited coral reef groupers ( Plectropomus maculatus and Plectropomus leopardus ) within and among three clusters of reefs separated by 60–220 km within the Great Barrier Reef Marine Park, Australia. A total of 69 juvenile P. maculatus and 17 juvenile P. leopardus (representing 6% and 9% of the total juveniles sampled, respectively) were genetically assigned to parent individuals on reefs within the study area. We identified both short‐distance larval dispersal within regions (200 m to 50 km) and long‐distance, multidirectional dispersal of up to ~250 km among regions. Dispersal strength declined significantly with distance, with best‐fit dispersal kernels estimating median dispersal distances of ~110 km for P. maculatus and ~190 km for P. leopardus . Larval exchange among reefs demonstrates that established reserves form a highly connected network and contribute larvae for the replenishment of fished reefs at multiple spatial scales. Our findings highlight the potential for long‐distance dispersal in an important group of reef fishes, and provide further evidence that effectively protected reserves can yield recruitment and sustainability benefits for exploited fish populations.

Limitations of outsourcing on‐the‐ground biodiversity conservation - Gwenllian D. Iacona; Michael Bode; Paul R. Armsworth (Conservation Biology, 2016)
To counteract global species decline, modern biodiversity conservation engages in large projects, spends billions of dollars, and includes many organizations working simultaneously within regions. To add to this complexity, the conservation sector has hierarchical structure, where conservation actions are often outsourced by funders (foundations, government, etc.) to local organizations that work on‐the‐ground. In contrast, conservation science usually assumes that a single organization makes resource allocation decisions. This discrepancy calls for theory to understand how the expected biodiversity outcomes change when interactions between organizations are accounted for. Here, we used a game theoretic model to explore how biodiversity outcomes are affected by vertical and horizontal interactions between 3 conservation organizations: a funder that outsourced its actions and 2 local conservation organizations that work on‐the‐ground. Interactions between the organizations changed the spending decisions made by individual organizations, and thereby the magnitude and direction of the conservation benefits. We showed that funders would struggle to incentivize recipient organizations with set priorities to perform desired actions, even when they control substantial amounts of the funding and employ common contracting approaches to enhance outcomes. Instead, biodiversity outcomes depended on priority alignment across the organizations. Conservation outcomes for the funder were improved by strategic interactions when organizational priorities were well aligned, but decreased when priorities were misaligned. Meanwhile, local organizations had improved outcomes regardless of alignment due to additional funding in the system. Given that conservation often involves the aggregate actions of multiple organizations with different objectives, strategic interactions between organizations need to be considered if we are to predict possible outcomes of conservation programs or costs of achieving conservation targets.

Hyperstability masks declines in bumphead parrotfish (Bolbometopon muricatum) populations - Richard J. Hamilton; Glenn R. Almany; Don Stevens; Michael Bode; John Pita; Nate A. Peterson; J. Howard Choat (Coral Reefs, 2016)

Resolving future fire management conflicts using multicriteria decision making - Don A. Driscoll; Michael Bode; Ross A. Bradstock; David A. Keith; Trent D. Penman; Owen F. Price (Conservation Biology, 2016)
Management strategies to reduce the risks to human life and property from wildfire commonly involve burning native vegetation. However, planned burning can conflict with other societal objectives such as human health and biodiversity conservation. These conflicts are likely to intensify as fire regimes change under future climates and as growing human populations encroach farther into fire‐prone ecosystems. Decisions about managing fire risks are therefore complex and warrant more sophisticated approaches than are typically used. We applied a multicriteria decision making approach (MCDA) with the potential to improve fire management outcomes to the case of a highly populated, biodiverse, and flammable wildland–urban interface. We considered the effects of 22 planned burning options on 8 objectives: house protection, maximizing water quality, minimizing carbon emissions and impacts on human health, and minimizing declines of 5 distinct species types. The MCDA identified a small number of management options (burning forest adjacent to houses) that performed well for most objectives, but not for one species type (arboreal mammal) or for water quality. Although MCDA made the conflict between objectives explicit, resolution of the problem depended on the weighting assigned to each objective. Additive weighting of criteria traded off the arboreal mammal and water quality objectives for other objectives. Multiplicative weighting identified scenarios that avoided poor outcomes for any objective, which is important for avoiding potentially irreversible biodiversity losses. To distinguish reliably among management options, future work should focus on reducing uncertainty in outcomes across a range of objectives. Considering management actions that have more predictable outcomes than landscape fuel management will be important. We found that, where data were adequate, an MCDA can support decision making in the complex and often conflicted area of fire management.

Minimizing the Cost of Keeping Options Open for Conservation in a Changing Climate - MORENA MILLS; SAM NICOL; JESSIE A. WELLS; JOSÉ J. LAHOZ‐MONFORT; BRENDAN WINTLE; MICHAEL BODE; MARTIN WARDROP; TERRY WALSHE; WILLIAM J. M. PROBERT; MICHAEL C. RUNGE; HUGH P. POSSINGHAM; EVE MCDONALD MADDEN (Conservation Biology, 2014)
Policy documents advocate that managers should keep their options open while planning to protect coastal ecosystems from climate‐change impacts. However, the actual costs and benefits of maintaining flexibility remain largely unexplored, and alternative approaches for decision making under uncertainty may lead to better joint outcomes for conservation and other societal goals. For example, keeping options open for coastal ecosystems incurs opportunity costs for developers. We devised a decision framework that integrates these costs and benefits with probabilistic forecasts for the extent of sea‐level rise to find a balance between coastal ecosystem protection and moderate coastal development. Here, we suggest that instead of keeping their options open managers should incorporate uncertain sea‐level rise predictions into a decision‐making framework that evaluates the benefits and costs of conservation and development. In our example, based on plausible scenarios for sea‐level rise and assuming a risk‐neutral decision maker, we found that substantial development could be accommodated with negligible loss of environmental assets. Characterization of the Pareto efficiency of conservation and development outcomes provides valuable insight into the intensity of trade‐offs between development and conservation. However, additional work is required to improve understanding of the consequences of alternative spatial plans and the value judgments and risk preferences of decision makers and stakeholders. Minimizando el Costo de Mantener Opciones Abiertas para la Conservación en un Clima Cambiante

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

A physical map of the Chinese chestnut (Castanea mollissima) genome and its integration with the genetic map - Guang-Chen Fang; Barbara P. Blackmon; Margaret E. Staton; C. Dana Nelson; Thomas L. Kubisiak; Bode A. Olukolu; David Henry; Tatyana Zhebentyayeva; Christopher A. Saski; Chun-Huai Cheng; Megan Monsanto; Stephen Ficklin; et al. (Tree Genetics & Genomes, 2013)

Conservation Planning with Multiple Organizations and Objectives - MICHAEL BODE; WILL PROBERT; WILL R. TURNER; KERRIE A. WILSON; OSCAR VENTER (Conservation Biology, 2011)
There has been a dramatic increase in the number of conservation organizations worldwide. It is now common for multiple organizations to operate in the same landscape in pursuit of different conservation goals. New objectives, such as maintenance of ecosystem services, will attract additional funding and new organizations to conservation. Systematic conservation planning helps in the design of spatially explicit management actions that optimally conserve multiple landscape features (e.g., species, ecosystems, or ecosystem services). But the methods used in its application implicitly assume that a single actor implements the optimal plan. We investigated how organizational behavior and conservation outcomes are affected by the presence of autonomous implementing organizations with different objectives. We used simulation models and game theory to explore how alternative behaviors (e.g., organizations acting independently or explicitly cooperating) affected an organization's ability to protect their feature of interest, and investigated how the distribution of features in the landscape influenced organizations’ attitudes toward cooperation. Features with highly correlated spatial distributions, although typically considered an opportunity for mutually beneficial conservation planning, can lead to organizational interactions that result in lower levels of protection. These detrimental outcomes can be avoided by organizations that cooperate when acquiring land. Nevertheless, for cooperative purchases to benefit both organizations’ objectives, each must forgo the protection of land parcels that they would consider to be of high conservation value. Transaction costs incurred during cooperation and the sources of conservation funding could facilitate or hinder cooperative behavior.

Safeguarding Biodiversity and Ecosystem Services in the Little Karoo, South Africa - BENIS N. EGOH; BELINDA REYERS; JOSIE CARWARDINE; MICHAEL BODE; PATRICK J. O'FARRELL; KERRIE A. WILSON; HUGH P. POSSINGHAM; MATHIEU ROUGET; WILLEM De LANGE; DAVID M. RICHARDSON; RICHARD M. COWLING (Conservation Biology, 2010)
Global declines in biodiversity and the widespread degradation of ecosystem services have led to urgent calls to safeguard both. Responses to this urgency include calls to integrate the needs of ecosystem services and biodiversity into the design of conservation interventions. The benefits of such integration are purported to include improvements in the justification and resources available for these interventions. Nevertheless, additional costs and potential trade‐offs remain poorly understood in the design of interventions that seek to conserve biodiversity and ecosystem services. We sought to investigate the synergies and trade‐offs in safeguarding ecosystem services and biodiversity in South Africa's Little Karoo. We used data on three ecosystem services—carbon storage, water recharge, and fodder provision—and data on biodiversity to examine several conservation planning scenarios. First, we investigated the amount of each ecosystem service captured incidentally by a conservation plan to meet targets for biodiversity only while minimizing opportunity costs. We then examined the costs of adding targets for ecosystem services into this conservation plan. Finally, we explored trade‐offs between biodiversity and ecosystem service targets at a fixed cost. At least 30% of each ecosystem service was captured incidentally when all of biodiversity targets were met. By including data on ecosystem services, we increased the amount of services captured by at least 20% for all three services without additional costs. When biodiversity targets were reduced by 8%, an extra 40% of fodder provision and water recharge were obtained and 58% of carbon could be captured for the same cost. The opportunity cost (in terms of forgone production) of safeguarding 100% of the biodiversity targets was about US$500 million. Our results showed that with a small decrease in biodiversity target achievement, substantial gains for the conservation of ecosystem services can be achieved within our biodiversity priority areas for no extra cost.

How to Build an Efficient Conservation Fence - MICHAEL BODE; BRENDAN WINTLE (Conservation Biology, 2010)
Barriers are used to achieve diverse objectives in conservation and biosecurity. In conservation management, fences are often erected to exclude introduced predators and to contain diseased animals or invasive species. Planning an efficient conservation fence involves a number of decisions, including the size and design of the enclosure. We formulated the first general framework for building a fence that minimizes long‐term management costs by balancing the expense of constructing a more secure barrier against the costs of coping with more frequent failures. The approach systematically considers the range of potential solutions to a well‐defined fencing problem and results in a solution that maximizes conservation return on investment. We illustrated this method by designing efficient fences to address two different conservation goals: exclusion of invasive predators from populations of threatened eastern barred bandicoots ( Perameles gunnii ) and maintenance of isolated populations of healthy Tasmanian devils ( Sarcophilus harrisii ). A systematic approach to conservation fencing allows the best fence design to be chosen quantitatively and defensibly. It also facilitates conservation decisions at a strategic level by allowing fencing to be compared transparently with alternative conservation management actions.

Dynamic marine protected areas can improve the resilience of coral reef systems - Edward T. Game; Michael Bode; Eve McDonald‐Madden; Hedley S. Grantham; Hugh P. Possingham (Ecology Letters, 2009)
Ecology Letters (2009) 12: 1336–1346 Abstract Marine Protected Areas are usually static, permanently closed areas. There are, however, both social and ecological reasons to adopt dynamic closures, where reserves move through time. Using a general theoretical framework, we investigate whether dynamic closures can improve the mean biomass of herbivorous fishes on reef systems, thereby enhancing resilience to undesirable phase‐shifts. At current levels of reservation (10–30%), moving protection between all reefs in a system is unlikely to improve herbivore biomass, but can lead to a more even distribution of biomass. However, if protected areas are rotated among an appropriate subset of the entire reef system (e.g. rotating 10 protected areas between only 20 reefs in a 100 reef system), dynamic closures always lead to increased mean herbivore biomass. The management strategy that will achieve the highest mean herbivore biomass depends on both the trajectories and rates of population recovery and decline. Given the current large‐scale threats to coral reefs, the ability of dynamic marine protected areas to achieve conservation goals deserves more attention.

Tracing Roman lead sources using lead isotope analyses in conjunction with archaeological and epigraphic evidence—a case study from Augustan/Tiberian Germania - Michael Bode; Andreas Hauptmann; Klaus Mezger (Archaeological and Anthropological Sciences, 2009)

Organization of the amplified type I interferon gene cluster and associated chromosome regions in the interphase nucleus of human osteosarcoma cells - Michael J. Zeitz; Narasimharao V. Marella; Kishore S. Malyavantham; Sandra Goetze; Juergen Bode; Ivan Raska; Ronald Berezney (Chromosome Research, 2009)

Ladder-like amplification of the type I interferon gene cluster in the human osteosarcoma cell line MG63 - Narasimharao V. Marella; Michael J. Zeitz; Kishore S. Malyavantham; Artem Pliss; Sei-ichi Matsui; Sandra Goetze; Juergen Bode; Ivan Raska; Ronald Berezney (Chromosome Research, 2008)

The need for speed: informed land acquisitions for conservation in a dynamic property market - Eve McDonald‐Madden; Michael Bode; Edward T. Game; Hedley Grantham; Hugh P. Possingham (Ecology Letters, 2008)
Land acquisition is a common approach to biodiversity conservation but is typically subject to property availability on the public market. Consequently, conservation plans are often unable to be implemented as intended. When properties come on the market, conservation agencies must make a choice: purchase immediately, often without a detailed knowledge of its biodiversity value; survey the parcel and accept the risk that it may be removed from the market during this process; or not purchase and hope a better parcel comes on the market at a later date. We describe both an optimal method, using stochastic dynamic programming, and a simple rule of thumb for making such decisions. The solutions to this problem illustrate how optimal conservation is necessarily dynamic and requires explicit consideration of both the time period allowed for implementation and the availability of properties.

Incorporating the Effects of Socioeconomic Uncertainty into Priority Setting for Conservation Investment - MARISSA F. McBRIDE; KERRIE A. WILSON; MICHAEL BODE; HUGH P. POSSINGHAM (Conservation Biology, 2007)
Uncertainty in the implementation and outcomes of conservation actions that is not accounted for leaves conservation plans vulnerable to potential changes in future conditions. We used a decision‐theoretic approach to investigate the effects of two types of investment uncertainty on the optimal allocation of global conservation resources for land acquisition in the Mediterranean Basin. We considered uncertainty about (1) whether investment will continue and (2) whether the acquired biodiversity assets are secure, which we termed transaction uncertainty and performance uncertainty, respectively. We also developed and tested the robustness of different rules of thumb for guiding the allocation of conservation resources when these sources of uncertainty exist. In the presence of uncertainty in future investment ability (transaction uncertainty), the optimal strategy was opportunistic, meaning the investment priority should be to act where uncertainty is highest while investment remains possible. When there was a probability that investments would fail (performance uncertainty), the optimal solution became a complex trade‐off between the immediate biodiversity benefits of acting in a region and the perceived longevity of the investment. In general, regions were prioritized for investment when they had the greatest performance certainty, even if an alternative region was highly threatened or had higher biodiversity value. The improved performance of rules of thumb when accounting for uncertainty highlights the importance of explicitly incorporating sources of investment uncertainty and evaluating potential conservation investments in the context of their likely long‐term success.